Non‐radiological method for three‐dimensional implant position evaluation using an intraoral scan method. Issue 9 (26th June 2013) - von See, Constantin; Wagner, Maximilian E. H.; Schumann, Paul; Lindhorst, Daniel; Gellrich, Nils‐Claudius; Stoetzer, Marcus
Abstract Introduction This technical innovation presents a method that reproduces the position of a dental implant after insertion without the reuse of X‐ray radiation. Material and Methods An implant was inserted into the natural gap between the canines and premolars of three domestic pigs. A Straumann Scanbody was then screwed to the implant, and a digital impression of the jaw segment was made. The scanbody was scanned using a hand‐held scanner. This was followed by the radiological detection of implant position on a CBCT. On the computer, the position of the implant was calculated and compared with the radiologically detected position. Results The calculated and determined position of the dental implant by the scanner is in good agreement with the radiologically controlled position. Discussion Evaluating the position of implants using intraoral scans is an easy and radiation‐free method of three‐dimensional site assessment after superimposition over a three‐dimensional data set.